Two kinds of traditional Chinese medicine prescriptions reduce thymic inflammation levels and improve humoral immunity of finishing pigs - Wang, Xiaoyu; Chen, Jiajia; Yang, Fan; Ali, Farah; Mao, Yaqin; Hu, Aiming; Xu, Tianfang; Yang, Yan; Wang, Feibing; Zhou, Guangbin; Guo, Xiaowang; Cao, Huabin (Frontiers in Veterinary Science, 2022)
In animal husbandry, traditional Chinese medicine (TCM) as a reasonable alternative to antibiotics has attracted more and more concern in order to reduce microbial resistance. This study was aimed to investigate the effects of dietary supplementation with TCM prescriptions on serum parameters and thymus inflammation responses in finishing pigs. Thirty finishing pigs were randomly divided into three groups, which includes Con group (basal diet), TCM1 group (basal diet supplemented with XiaoJianZhong prescriptions) and TCM2 group (basal diet supplemented with Jingsananli-sepsis). Results showed that the contents of C3 and C4 in serum were significantly increased in both TCM1 and TCM2 group compared to Con group on day 30. Similarly, the levels of IgA, IgG and IgM were increased in TCM2 group, and only the level of IgM in TCM1 were increased on day 30. Meanwhile, the levels of classical swine fever virus (CSFV) and respiratory syndrome virus (PRRSV) antibody have a notable increasing in TCM1 and TCM2 group. Both TCM1 and TCM2 inhibited the levels of TLR4/MyD88/NF-κB signaling pathway related mRNA (TLR4, MyD88, NF-κB, IL6, IL8 and TNF-α) and protein (p-IκBα and p-P65) expression in the thymus. In conclusion, dietary supplementation with TCM can reduce thymic inflammation levels and improve humoral immunity of finishing pigs.